Kinetics of the premelting (L beta'-P beta') and main transition (P beta'-L alpha) in hydrated dipalmitoylphosphatidylcholine. A time-resolved x-ray diffraction study using microwave-induced temperature-jumps. - Caffrey, M (1990)
The dynamics and mechanism of the premelting (L beta'-P beta') and main transitions (P beta'-L alpha) in fully hydrated dipalmitoylphosphatidylcholine were examined by low-angle time-resolved x-ray diffraction (TRXRD) using microwave radiation to effect uniform, internal sample heating. Equilibrium and dynamic aspects of the transitions were investigated. The dynamic studies involved applying a temperature jump of sufficient amplitude to effect the two transitions sequentially. Our findings are as follows. (a) Microwave radiation has proven useful as a means for implementing rapid and uniform internal heating in temperature-jump studies of lipid-phase transition kinetics. (b) Heating rate can be controlled by adjusting microwave power setting. (c) The thermal expansion coefficient of the three lyotropic phases follows the sequence L beta' not equal to O greater than P beta' much greater than L alpha. (d) Regardless of temperature-jump amplitude and sample heating rate the P beta' phase was always in evidence as an intermediate between the L beta' and L alpha phases. (e) The degree of development of the P beta' phase was inversely proportional to temperature-jump amplitude and heating rate. (f) The shortest transit time recorded for the combined L beta'-P beta', and P beta'-L alpha transitions was less than 1 s. (g) Upon cooling from the L alpha phase the onset of the chain disorder/order transition was apparent as a dramatic change of slope in the scattering angle vs. time plot which is interpreted as arising from sample heating by the latent heat of the transition. (h) Based on the shape of the low-angle diffraction pattern of the P beta' phase the P beta'-L alpha transition appears to be reversible with no evidence of metastability as was observed in the slow scan TRXRD measurements of Tenchov et al. (1989. Biophys. J. 56:757-768).